Taxonomic and chemical assessment of exceptionally abundant rock mine biofilm - Tomczyk-Żak, Karolina; Szczesny, Paweł; Gromadka, Robert; Zielenkiewicz, Urszula (PeerJ, 2017)
Background An exceptionally thick biofilm covers walls of ancient gold and arsenic Złoty Stok mine (Poland) in the apparent absence of organic sources of energy. Methods and Results We have characterized this microbial community using culture-dependent and independent methods. We sequenced amplicons of the 16S rRNA gene obtained using generic primers and additional primers targeted at Archaea and Actinobacteria separately. Also, we have cultured numerous isolates from the biofilm on different media under aerobic and anaerobic conditions. We discovered very high biodiversity, and no single taxonomic group was dominant. The majority of almost 4,000 OTUs were classified above genus level indicating presence of novel species. Elemental analysis, performed using SEM-EDS and X-ray, of biofilm samples showed that carbon, sulphur and oxygen were not evenly distributed in the biofilm and that their presence is highly correlated. However, the distribution of arsenic and iron was more flat, and numerous intrusions of elemental silver and platinum were noted, indicating that microorganisms play a key role in releasing these elements from the rock. Conclusions Altogether, the picture obtained throughout this study shows a very rich, complex and interdependent system of rock biofilm. The chemical heterogeneity of biofilm is a likely explanation as to why this oligotrophic environment is capable of supporting such high microbial diversity.
Keywords: Biodiversity; Metagenomics; Mine; Biofilm